Improving the photocurrent of a PBDTTT-CF and PCBM based organic thin film photoconductor by forming a bilayer structure. Issue 103 (6th October 2015) - Jin, Zhiwen; Zhou, Qing; Mao, Peng; Wang, Aiji; Shang, Boyang; Wang, Yinshu; Li, Hui; Wang, Jizheng
Abstract : By controlling and adjusting the fabrication process, all-solution-processed bilayer OTFPs exhibits a faster carrier transport which greatly enhanced the photocurrent. Abstract : The performance of traditional organic thin film photoconductors (OTFPs) is limited by the low carrier mobility in the donor : acceptor (D : A) blend film. To overcome such a problem, a higher-mobility carrier transport layer should be included in the D : A blend based device. However doing so will certainly result in a bilayer or even multilayer structure, which is usually a challenge for all-solution processing methods. Here by carefully controlling and adjusting the fabrication process, an all-solution-processed PBDTTT-CF/PBDTTT-CF : PCBM bilayer OTFP is demonstrated. In such a bilayer device, the PBDTTT-CF : PCBM blend layer is responsible for light absorption and free photo carrier generation, and the underlying PBDTTT-CF layer is responsible for the photo carrier transport inside the device. The hole mobility in the PBDTTT-CF layer is measured to be 9.1 × 10 −4 cm 2 V −1 s −1, much higher than that in the PBDTTT-CF : PCBM blend film, which is only 4.3 × 10 −5 cm 2 V −1 s −1 . As a result of the faster carrier transport, the bilayer device exhibits a greatly enhanced photocurrent, which is about 7 times higher than that of the single blend layer device. Meanwhile, the on/off response of the bilayer device is also improved, which is shorter than 0.1/0.1 s.